Lung cancer risk among nonsmoking women in relation to diet and physical activity - Kubík, A; Zatloukal, P; Tomásek, L; Pauk, N; Petruzelka, L; Plesko, I (Neoplasma, 2004)
To investigate the relationship between diet, physical activity, and the risk of lung cancer among female nonsmokers, and to compare it with female smokers in the same population, we conducted a case-control study. Data collected by personal interviews from 419 cases and 1593 controls were analyzed using unconditional logistic regression. As expected, among 130 nonsmoking cases, adenocarcinoma was the predominant cell type (49.2%), followed by squamous cell (20.2%) and small cell cancers (10.5%). The corresponding figures for 289 smoking cases were 29.3%, 27.5%, and 28.2%, respectively. Excess lung cancer risk was associated with consumption of red meat among nonsmokers (OR=2.20, 95%CI 1.07--4.51). Protective effects were observed for vegetables (OR=0.61, 95%CI 0.39--0.96), apples (OR=0.67, 95%CI 0.48--0.95), milk/dairy products (OR=0.54, 95%CI 0.32--0.93), coffee (OR=0.56, 95%CI 0.34--0.91), and wine (OR=0.69, 95%CI 0.49--0.98) among smokers only, and for black tea (OR=0.67, 95%CI 0.46--0.99) among nonsmokers only. An inverse association with risk emerged for physical exercise (or sport, walking), among smokers only. Some items of diet and physical activity appear to be important factors contributing to variation in lung cancer risk among women in the Czech Republic, however, their effects in nonsmokers may differ from those in smokers.
Keywords: Logistic Models; společenská třída; Social Class; nádory plic; odds ratio; Lung Neoplasms; Adult; Age Factors; Aged; dospělí; Case-Control Studies; senioři; Exercise; Smoking; dieta; logistické modely; senioři nad 80 let; lidé; ženské pohlaví; studie případů a kontrol; Humans; věkové faktory; Aged, 80 and over; Diet; Risk; Odds Ratio; Female; cvičení; riziko; lidé středního věku; kouření; Middle Aged